Characteristic of plywood using wood mahagony bark powder as veneer bonding agent at several storage life - Mustamin, Nurfianah; Suhasman, S; Yunianti, Andi Detti; Arisandi, Heru; Agussalim, A (Jurnal Penelitian Kehutanan Wallacea, 2022)
Several barks from certain species, such as mahogany, have a relatively high tannin compound content. These tannin compounds have several hydroxyl groups that can be oxidized to produce radical groups. These radical groups can bind to wood chemical components through bonding mechanisms, such as esterification and phenoxy radicals coupling. The use of oxidized bark as a bonding agent has shown good characteristics of plywood. However, this method will have a problem, in terms of storage life, when being applied at industrial scale. The purpose of this study was to investigate the possible application of oxidized mahagony bark powder as a bonding agent for producing plywood and evaluate the relationship between storage life and the quality of bonding agent stock in the form of oxidized bark powder. The bark powder was oxidized using hydrogen peroxide and a catalyst. The oxidized powder was stored for 0 days, 1 day, 1 week (7 days), and 1 month (30 days) in a tightly closed container before being applied for the plywood manufacture. The tests carried out were physical and mechanical properties of plywood. The results showed that the physical properties of plywood using oxidized mahagony bark powder as a bonding agent with various storage periods have met SNI 5008.2:2016. However, the mechanical properties of the produced plywood were still below the standard. The results indicated that technology for producing plywood using oxidized bark powder is potential for further development